Hard tissue formation in pulpotomized primary teeth in dogs with nanomaterials MCM-48 and MCM-48/hydroxyapatite: an in vivo animal study - Sahar Talebi; Nosrat Nourbakhsh; Ardeshir Talebi; Amir Abbas Nourbakhsh; Abbas Haghighat; Maziar Manshayi; Hamid Reza Bakhsheshi; Razieh Karimi; Rahman Nazeri; Kenneth J.D. Mackenzie (BMC, 2024)
Abstract Background This animal study sought to evaluate two novel nanomaterials for pulpotomy of primary teeth and assess the short-term pulpal response and hard tissue formation in dogs. The results were compared with mineral trioxide aggregate (MTA). Methods This in vivo animal study on dogs evaluated 48 primary premolar teeth of 4 mongrel female dogs the age of 6-8 weeks, randomly divided into four groups (n = 12). The teeth underwent complete pulpotomy under general anesthesia. The pulp tissue was capped with MCM-48, MCM-48/Hydroxyapatite (HA), MTA (positive control), and gutta-percha (negative control), and the teeth were restored with intermediate restorative material (IRM) paste and amalgam. After 4-6 weeks, the teeth were extracted and histologically analyzed to assess the pulpal response to the pulpotomy agent. Results The data were analyzed using the Kruskal‒Wallis, Fisher's exact, Spearman's, and Mann‒Whitney tests. The four groups were not significantly different regarding the severity of inflammation (P = 0.53), extent of inflammation (P = 0.72), necrosis (P = 0.361), severity of edema (P = 0.52), extent of edema (P = 0.06), or connective tissue formation (P = 0.064). A significant correlation was noted between the severity and extent of inflammation (r = 0.954, P < 0.001). The four groups were significantly different regarding the frequency of bone formation (P = 0.012), extent of connective tissue formation (P = 0.047), severity of congestion (P = 0.02), and extent of congestion (P = 0.01). No bone formation was noted in the gutta-percha group. The type of newly formed bone was not significantly different among the three experimental groups (P = 0.320). Conclusion MCM-48 and MCM-48/HA are bioactive nanomaterials that may serve as alternatives for pulpotomy of primary teeth due to their ability to induce hard tissue formation. The MCM-48 and MCM-48/HA mesoporous silica nanomaterials have the potential to induce osteogenesis and tertiary (reparative) dentin formation.